White Matter Microstructural Organization Is Higher with Age in Adult Superior Cerebellar Peduncles - Kanaan, Richard A.; Allin, Matthew; Picchioni, Marco M.; Shergill, Sukhwinder S.; McGuire, Philip K. (Frontiers in Aging Neuroscience, 2016)
Using diffusion tensor imaging, we conducted an exploratory investigation of the relationship between white matter tract microstructure and age in 200 healthy subjects using tract-based spatial statistics (TBSS). Though most tracts showed the slight decline widely noted, microstructural organization in both superior cerebellar peduncles (SCP) correlated positively with age, a result not previously reported. We confirmed this by using an alternative method, and by repeating our TBSS analysis in an additional sample of 133 healthy subjects. In exploring this surprising result we considered the possibility that this might arise from the continual cognitive and motor refinement that is enacted in the cerebellum: we found that tract microstructure in both SCPs was also strongly correlated with IQ, again in contrast with all other tracts, and its relationship with age mediated by IQ, as a training model would predict.